THE ROLE OF SPECIALIZAD TRAINING COURSES TO IMPROVE THE PERFORMANCE OF EMPLOYEES IN THE FIELD OF ANIMAL RESOURCES IN CENTRAL GOVWRNORATES OF IRAQ - & Al-Lmashadany, Al-azzawy (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
The research aiming  to identify the role of the specialist training courses in improving the workers' performance at animal resources in provinces of the middle region of Iraq , via measures included 78 items distributed on 5 topics as follow: the specialist  training  courses reality, keep up agricultural innovations courses,  the contribution of the specialist training courses, obstacles hindering the training  courses to improve the workers in the animal resources, And how to reduce these obstacles. Research community workers in animal resources who have received specialized training courses for the period from 2012 _ 2014 consists amounted 339 distributed in eight provinces at the middle region of Iraq, The exclusion of the provinces of Salahaddin and Anbar for the poor security conditions at time of data collection, And it has become the provinces covered by the search (Baghdad, Diyala, Karbala, Najaf, Wasit, Babil). an random sample 66% was  taken  from the workers in the animal resource of from four provinces (Baghdad, Diyala, Karbala and Najaf ) and random sample was taken of 40% of 136 researched, For the purpose of realize the objectives of the research, it has been preparing a questionnaire to collect data from respondents, which included a five-scale composed of 78 items distributed on five topics as follow : the specialist training courses reality 13 items, , keep up agricultural innovations courses 10 items, contribution of the training courses in improving the workers 'performance 21 items, obstacles hindering the training courses in improving the workers' performance 18 items, methods of obstacles limitation 16 items. The results concluded that the training courses contribute essential role in improving the performance of workers, keep up the training courses innovations in the animal resources, lack of financial allocations provided to the training centers